Analysing the relationship between residential property prices and their determinants: a semiparametric geographically weighted regression approach - Dziauddin Mohd Faris, Ismail Kamarul, Othman Zainudin, (N/A, 2014)
Analysing the relationship between residential property prices and their determinants: a semiparametric geographically weighted regression approach by Dziauddin Mohd Faris, Ismail Kamarul, Othman Zainudin,